Understanding and Managing Harmful Algal Bloom Risks in a Changing Climate: Lessons From the European CoCliME Project - West, Jennifer Joy; Järnberg, Linn; Berdalet, Elisa; Cusack, Caroline (Frontiers in Climate, 2021)
This paper discusses the conceptual and methodological challenges to co-developing high-quality and transferable knowledge to understand and manage harmful algal bloom (HAB) risks as part of adaptation to changing aquatic ecosystems in Europe. Global HAB-climate change research efforts to date have focused on enhancing the credibility of scientific knowledge by conducting basic scientific research aimed at understanding the physical and biogeochemical drivers and mechanisms shaping HAB dynamics in order to predict their occurrence and prevent their societal and ecological impacts. However, the rapid and interconnected changes occurring in marine ecosystems worldwide necessitate a simultaneous shift towards enhancing the salience, legitimacy, usefulness and usability of this knowledge for decision-making. To address this need, we present and discuss empirical findings from the marine-focused CoCliME project, which set out to co-develop user-oriented climate services to support HAB risk mitigation and adaptation in European coastal regions. We present lessons learned in relation to four areas of project implementation, across five regional cases, that emerged as essential for enhancing the quality of knowledge for managing HAB-climate risks: 1) Engaging stakeholders to understand their knowledge, experiences, interests and concerns; 2) Co-developing a shared terminology and framing of the “HAB-related problems”; 3) Advancing scientific understanding of drivers and interactions shaping HAB-climate risks and; 4) Co-producing prototype services that integrate social and HAB-climate data and knowledge to support decision-making. We find that efforts to reduce scientific knowledge gaps and uncertainties about HAB-climate linkages (efforts to enhance credibility), while important, risk overlooking key aspects of knowledge co-production and application that are necessary to render this knowledge more salient, legitimate, useful and usable. Understanding the multi-risk decision-making context within which societal stakeholders appraise HABs and climate change risks and approaching knowledge co-production as a learning process, are key lessons learned in this respect. Drawing on project learning, we highlight key priorities for enhancing the societal relevance and impact of HABs-climate research during the UN Decade of Ocean Science for Sustainable Development.